2021
DOI: 10.12659/ajcr.934083
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Cefepime-Induced Neurotoxicity in a Patient with End-Stage Renal Disease

Abstract: Patient: Female, 86-year-old Final Diagnosis: Drug reaction Symptoms: Encephalopathy • seizure Medication: — Clinical Procedure: — Specialty: Neurology Objective: Unusual clinical course Background: Cefepime, a fourth-generation cephalosporin, has a known adverse effect of neurotoxicity. It occurs notably in patients with end-stage renal disease, but symptom resolution typically occurs within a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Reliable data strongly support the early initiation of hemodialysis to expedite removal of cefepime from the circulation, leading to accelerated recovery and a favorable prognosis. 12 , 19 , 23 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable data strongly support the early initiation of hemodialysis to expedite removal of cefepime from the circulation, leading to accelerated recovery and a favorable prognosis. 12 , 19 , 23 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Reliable data strongly support the early initiation of hemodialysis to expedite removal of cefepime from the circulation, leading to accelerated recovery and a favorable prognosis. 12,19,23,28,29 Anticonvulsant therapy, primarily consisting of benzodiazepines along with alternatives such as phenobarbital, phenytoin, levetiracetam, and valproic acid, is occasionally administered to patients with CIN. However, benzodiazepines do not lead to immediate or permanent restoration of patients' mental state or EEG patterns, although EEG studies have demonstrated temporary suppression of generalized periodic discharges following benzodiazepine injection.…”
Section: Discussionmentioning
confidence: 99%
“…Renal impairment reduces the clearance of cefepime, leading to drug accumulation in the body and increasing susceptibility to neurotoxicity. 2 , 11 Even with renal dose adjustments, cefepime demonstrates notable adverse effects. In 2013, Fugate et al assessed 100 intensive care unit patients for neurotoxicity, identifying 15 likely cases of CIE and 7 definite cases.…”
Section: Discussionmentioning
confidence: 99%
“…In many previous studies of piperacillin/tazobactam, the incidence of nephrotoxicity tended to increase, especially when this combination was used with vancomycin concomitantly [ 30 , 31 ]. Cefepime has been known to be associated with adverse neurologic effects [ 32 , 33 ] and an increased incidence of hospital-acquired Clostridioides difficile infection [ 34 ]. The well-known adverse effects of these two types of antibiotics differ, but these effects were not described among the KNHIS data.…”
Section: Discussionmentioning
confidence: 99%